Development of nasal allergen challenge with cockroach in children with asthma. Issue 5 (20th March 2021) - Rudman Spergel, Amanda K.; Sever, Michelle L.; Johnson, Jacqueline; Gill, Michelle A.; Schulten, Veronique; Frazier, April; Kercsmar, Carolyn M.; Lovinsky‐Desir, Stephanie; Searing, Dan A.; Sette, Alessandro; Shao, Baomei; Teach, Stephen J.; et al.
Abstract: Background: Nasal allergen challenge (NAC) could be a means to assess indication and/or an outcome of allergen‐specific therapies, particularly for perennial allergens. NACs are not commonly conducted in children with asthma, and cockroach NACs are not well established. This study's objective was to identify a range of German cockroach extract doses that induce nasal symptoms and to assess the safety of cockroach NAC in children with asthma. Methods: Ten adults (18‐37 years) followed by 25 children (8‐14 years) with well‐controlled, persistent asthma and cockroach sensitization underwent NAC with diluent followed by up to 8 escalating doses of cockroach extract (0.00381‐11.9 µg/mL Bla g 1 ). NAC outcome was determined by Total Nasal Symptom Score (TNSS) and/or sneeze score. Cockroach allergen–induced T‐cell activation and IL‐5 production were measured in peripheral blood mononuclear cells. Results: 67% (6/9) of adults and 68% (17/25) of children had a positive NAC at a median response dose of 0.120 µg/mL [IQR 0.0380‐0.379 µg/mL] of Bla g 1 . Additionally, three children responded to diluent alone and did not receive any cockroach extract. Overall, 32% (11/34) were positive with sneezes alone, 15% (5/34) with TNSS alone, and 21% (7/34) with both criteria. At baseline, NAC responders had higher cockroach‐specific IgE ( P  = .03), lower cockroach‐specific IgG/IgE ratios (children, P  = .002), and increased cockroach‐specific IL‐5–producing T lymphocytes ( P  = .045). The NAC was well tolerated. Conclusion: We report the methodology of NAC development for children with persistent asthma and cockroach sensitization. This NAC could be considered a tool to confirm clinically relevant sensitization and to assess responses in therapeutic studies.